2016
DOI: 10.1177/1558944716661994
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid Nonunion With Poor Prognostic Factors

Abstract: Background: To report on the results of free medial femoral condyle (MFC) vascularized bone graft for scaphoid nonunions with 1 or more poor prognostic factors. Methods: We have used the free MFC vascularized bone graft for scaphoid nonunions that have 1 or more factors associated with a poor prognosis. These were, a delay in presentation of over 5 years, a proximal pole nonunion, the presence of avascular necrosis (AVN), or previous nonunion surgery. We used this technique on 20 patients over a 4.5-year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The well-known poor prognostic factors in scaphoid nonunion are proximal pole nonunion, chronicity, unstable fixation, and AVN [4,9]. Jones et al [16] analyzed the prognostic factors that may influence the outcome of scaphoid nonunion and determined AVN and previous surgery for nonunion as poor prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The well-known poor prognostic factors in scaphoid nonunion are proximal pole nonunion, chronicity, unstable fixation, and AVN [4,9]. Jones et al [16] analyzed the prognostic factors that may influence the outcome of scaphoid nonunion and determined AVN and previous surgery for nonunion as poor prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al [16] analyzed the prognostic factors that may influence the outcome of scaphoid nonunion and determined AVN and previous surgery for nonunion as poor prognostic factors. Another study reported that outcomes are less favorable when nonunion is older than 5 years and in the presence of advanced degenerative changes [4]. The most important factors are known to be the site of pseudoarthrosis and the viability of the proximal pole due to the particularities of dual blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations